2020
DOI: 10.1242/jcs.250597
|View full text |Cite
|
Sign up to set email alerts
|

The diverse roles and dynamic rearrangement of vimentin during viral infection

Abstract: Epidemics caused by viral infections pose a significant global threat. Cytoskeletal vimentin is a major intermediate filament (IF) protein, and is involved in numerous functions, including cell signaling, epithelial–mesenchymal transition, intracellular organization and cell migration. Vimentin has important roles for the life cycle of particular viruses; it can act as a co-receptor to enable effective virus invasion and guide efficient transport of the virus to the replication site. Furthermore, vimentin has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 125 publications
0
55
0
1
Order By: Relevance
“…The presence of vimentin has been reported to influence cell susceptibility to bacterial and viral pathogens, either in a positive or in a negative way, through various mechanisms, including behaving as an attachment factor at the cell membrane or influencing the replicative cycle [12,20,25,85,86]. Based on previous work on other coronaviruses, the potential role of vimentin in SARS-CoV-2 infection is currently a topic of interest [12,59,60], although the experimental evidence is so far limited.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of vimentin has been reported to influence cell susceptibility to bacterial and viral pathogens, either in a positive or in a negative way, through various mechanisms, including behaving as an attachment factor at the cell membrane or influencing the replicative cycle [12,20,25,85,86]. Based on previous work on other coronaviruses, the potential role of vimentin in SARS-CoV-2 infection is currently a topic of interest [12,59,60], although the experimental evidence is so far limited.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been growing interest in the biological function of vimentin (Menko 2014;Cheng 2016;Ghosh 2018;Patteson 2019;Li and Kuemmerle 2020;Li 2020;Zhang 2020;Suprewicz 2021). As a multifunctional protein, vimentin is differentially expressed in diverse cell types, whereby it may also play a tissue-speci c function.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Su et al (Su 2019) also reported a positive role of vimentin in lymphocyte apoptosis, which may serve as a potential serum biomarker for sepsis prognosis. Moreover, vimentin has also been proposed as a possible cellular target for the treatment of coronavirus disease 19 (COVID-19) (Li 2020;Zhang 2020). Because vimentin is suggested as a co-receptor for the entry of SARS-CoV-2 into cells, drugs that decrease the expression of vimentin can be used to treat patients with COVID-19 (Yu 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vimentin is a major intermediate filament and provides a cytoplasmic scaffold for the organization and functions of cellular organelles, and other cellular processes such as cell spreading, migration and signal transduction [ 177 ]. In addition, vimentin has been reported to actively support viral infections [ 178 ]. FMDV 3A has been identified as a binding partner for vimentin from mass spectrometry analysis of proteins that co-purified with 3A (using an anti-3A antibody) from FMDV-infected primary fetal bovine kidney (FBK) cells [ 179 ].…”
Section: Interactions With Cellular Proteinsmentioning
confidence: 99%